(3QSGdI aj Gdabgs - (3GdCSchFj, GdbQGLg OGZj, eMeO HGbQ Hf eMeO Sdje, cGf MjG(B: 1285(3g`s ((3YScQ Hf MSjf GdJHQjRjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3ajbhd GdMbjQ eMeO HGbQ Hf eMeO Sdje (B... (3Efg SCdfj HYV(B...s
(3BNQgG (B:s
(3hjfHZj QaYgG Edi GdabgGA GdEeGejI Ref GdZjHI(B... (3GYde HehGVYgG hdG jYWj GdabjQ GdhGMO Cbd ef UGY eY(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, (B156s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis